The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.culher.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced non-destructive techniques for the diagnosis of historic buildings: The Loka-Hteik-Pan temple in Bagan

Abstract: Cultural heritage is the foundation upon which global and historical values are based on. It connects us to the legacy left by our ancestors and identifies who we are as part of the modern society. Globally and specifically in the northeastern Romania, the landscape where cultural heritage sites were built on is constantly evolving due to mass wasting processes. Among these processes, landslide and gullies can disrupt the gravitational equilibrium directly or around these sites, threatening their very existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Furthermore, even when there is mortar between the units, weathering effects and lack of maintenance cause significant deterioration and often the total loss of the mortar, or at least of the loss of mortar-stone bond, over the lifetime of a structure, eventually rendering it similar to a dry-joint system. Recent and past earthquakes demonstrated that many of the unreinforced dry-joint and low-bond strength masonry structures are vulnerable to seismic actions and have been severely affected by past earthquakes [1][2][3]. Therefore, to better preserve, repair, and strengthen these structures, a thorough understanding of the DJ-SMW behavior under combined compression-shear forces is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even when there is mortar between the units, weathering effects and lack of maintenance cause significant deterioration and often the total loss of the mortar, or at least of the loss of mortar-stone bond, over the lifetime of a structure, eventually rendering it similar to a dry-joint system. Recent and past earthquakes demonstrated that many of the unreinforced dry-joint and low-bond strength masonry structures are vulnerable to seismic actions and have been severely affected by past earthquakes [1][2][3]. Therefore, to better preserve, repair, and strengthen these structures, a thorough understanding of the DJ-SMW behavior under combined compression-shear forces is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it is an issue of harmonising in a single system geometric and radiometric data which characterise the architectural/structural elements, according to a classification that is significant for structural purposes and enriching them with the content of diagnostic tests which together aim at assessing the state of health of the building and anti-seismic characteristics. Even if the multi-sensor techniques offered by the market today are particularly versatile in terms of information density and accuracy and quite adaptable to the infinite variety of materials and configurations of architectural complexes [ 38 ], some challenging aspects of digitisation are directly related to the structural conception devised by PL. Nervi for Torino Esposizioni.…”
Section: Goalsmentioning
confidence: 99%
“…Multi-site scanning can be performed on the inside and outside of cultural relic buildings. The scanned data must undergo data noise reduction processing to obtain a complete point cloud data model for heritage buildings [13][14][15][16][17] ("Fig. 3");  Next, it is to survey and map the decorative lines and patterns of heritage buildings on the spot, and combine historical data, literature and social and cultural background and other survey data to build a decorative pattern library of heritage buildings.…”
Section: B Construction Route Of Hbim Based On Point Cloud Datamentioning
confidence: 99%